Pharmacoeconomic analysis of anti-VEGF therapy for age-related macular degeneration - A. E. Cheberda; D. Yu. Belousov; M. M. Shishkin (Izdatelstvo OKI, 2018)
Diabetes mellitus (DM) is a widespread, severe disease that has outpaced many infectious and non-infectious diseases in terms of both incidence increases and economic burden in most developed countries. In addition to the direct threat to the health and well-being of patients, DM is associated with many severe complications. Among the most significant late complications of DM are diabetic retinopathy (DR) and diabetic macular edema (DME) which can lead to slow, persistent vision loss up to blindness. Significant progress in treating DME has been obtained after the role of vascular endothelium growth factor (VEGF) in the disease's pathophysiology became more understood, with several powerful clinical options emerging as result. Among the anti-VEGF drugs that have proven themselves well in clinical trials and practice with regards to treating DME are ranibizumab and aflibercept. Since there is currently relatively little understanding of their comparative pharmacoeconomic performance within context of Russian healthcare, the current pharmacoeconomic research (PHe) effort was undertaken. Aim. To perform comparative PHe analysis of ranibizumab and aflibercept for treatment of patients with DME in Russian Federation (RF). Methodology. A Markov model with 3 month long cycles, simulating the changes in patient's vision acuity was designed for this research effort. For each of the compared therapeutic alternative a simulated group of 1000 DME patients was constructed. The PHe analysis was performed from the point of view of Russian healthcare system within context of Mandatory Medical Insurance system and also from point of view of Russian budget as whole. Randomized controlled clinical trials investigating safety and efficacy of analyzed drugs were used as source of efficacy and safety data. Number of patients who avoided stage IV vision loss (blindness) was used as efficacy criterion. Time horizon of PHe analysis was set at 3 years. Costs were accounted based on existing treatment standards, and literature sources were used to link quality of life and vision acuity and then register QALY for various model states. Modelling results were used to carry out cost-effectiveness analysis (CEA), cost-utility analysis (CUA) and budget impact analysis (BIA). Two single-factor sensitivity analyses (SA) were used to ensure the results are robust to changes in market situation, and an additional analysis was undertaken to test for effects of choice of eye being treated (better seeing or worse seeing). Results. CEA indicated that ranibizumab administered using Pro Re Nata (PRN) regimen has best cost-efficacy, with lowest CER of 1 264 rub. Ranibizumab administered in Treat and Extend (T&E) regimen and aflibercept had higher CERs and thus inferior cost-efficacy (1 403 rub and 1667 rub respectively). The advantage of ranibizumab PRN extended to CUA, in which CUR was 554 rub for ranibizumab PRN, 616 rub for ranibizumab T&E and 729 rub for aflibercept. BIA performed per 100 000 population (accounted for prevalence of DM and DME epidemiology) has found that use of ranibizumab PRN instead of aflibercept could result in budget burden reduction of more than 17 million rubles per 3 years. All SA have confirmed result robustness. Conclusion. These results indicate that ranibizumab demonstrates favorable pharmacoeconomic properties and its further introduction into Russian clinical practice would allow to increase the efficacy of healthcare resource utilization in the RF.